IMPLEMENTATION OF MODEL-ELICITING ACTIVITIES TO IMPROVE THE ABILITY OF MATHEMATICAL PROBLEM SOLVING - Rubaitun Rubaitun (IKIP Siliwangi, 2018)
This study aims to determine whether the improvement of students' mathematical problem solving skills that get the learning of Model-Eliciting Activities is better than students who get regular learning. Method in this research is experiment and research design pretest and postest in experiment and control class. The population in this study were all students of MTs Kota Cimahi. School samples were taken at random, and obtained by MTs Negeri Kota Cimahi. Then the sample is selected two class VIII at random class. The experimental class uses Model-Eliciting Activities, while the control class uses ordinary learning. The hypothesis in this research is the improvement of student solving abilities of MTs students in Cimahi whose learning using Model-Eliciting Activities is better than using ordinary learning. Research data obtained through the instrument of posttest mathematical problem solving ability. The posttest data is processed by normality test, homogeneity test, and two average difference test using SPSS (Statistical Product and Service Solution) software version 16.0 for Windows. The results showed that the improvement of problem solving ability of MTs students in Cimahi whose learning using Model-Eliciting Activities was better than those using ordinary learning.